Impact of physical exercise on health and social interaction in older adults: a meta-analysis - Tao, Meng; Li, Shuang; Li, Luyao; Cao, Yuanyuan; Zhuang, Jie (Frontiers in Public Health, 2025)
BackgroundThis study aimed to evaluate the effect of physical exercise on the physical and mental health of older adults using meta-analysis and to analyze the moderating variables influencing this relationship. The goal was to provide a scientific basis for identifying effective exercise methods to enhance the physical and mental health of the older adults.MethodsA literature search was conducted in databases such as PubMed, Web of Science, Cochrane Library, and Google Scholar. Data were processed using Review Manager 5.4 and Stata 18.0 statistical software. Meta-analysis was performed using the random effects model, and relevant moderating variables were tested.ResultsThe study findings indicated that physical activity significantly improves the physical and mental health of older adults across various dimensions. Specifically, it showed a large effect size for enhancing social interactions (standardized mean difference (SMD) = 0.78, 95% confidence interval (CI) [0.14, 0.69], P = 0.0002), a medium effect size for improving physical health (SMD = 0.42, 95% CI [0.20, 0.48], P = 0.003), and a small effect size for improving mental health (SMD=0.34, 95% CI [0.37, 1.19], P < 0.001). All differences were statistically significant.ConclusionPhysical exercise has a positive impact on improving the physical and mental health of older adults, particularly in enhancing physical health, psychological well-being, and social interactions.